Ocular sarcoidosis, to screen or not to screen? - Leinonen, Sanna (Frontiers in Medicine, 2024)
Ocular sarcoidosis most commonly presents with symptoms and is first diagnosed before systemic sarcoidosis in at least half of the patients with sarcoidosis. Prevalence of ocular involvement in sarcoidosis varies between 2–80% depending on the study setting, included ocular diseases, and studied population. In many studies, ocular involvement in sarcoidosis has been overestimated mainly because study populations have been collected from eye clinics and because the study criteria have included ocular findings or symptoms that do not require treatment or monitoring. In a screening setting, asymptomatic ocular sarcoidosis has been detected in only 2–5%. 0–1% of the screened sarcoidosis patients have required treatment. For these reasons, ocular screening in sarcoidosis seems generally of little value. Patients with sarcoidosis who present with ocular symptoms should be screened for ocular sarcoidosis in a timely manner because they are at high risk of ocular disease.